Kontroversi Tambang Ormas Nahdlatul Ulama dalam Perspektif Ekonomi Islam: Sebuah Studi Netnografi - Dicko Syah Purnama Putra; Trischa Relanda Putra; Muhammad Ersya Faraby (Varied Knowledge Journal, 2026)
This study examines the controversy surrounding the Ormas Mining policy under Government Regulation No. 25 of 2024, which grants priority access to Special Mining Business Permit Areas (WIUPK) for religious community organizations (CSOs), particularly Nahdlatul Ulama (NU). The study aims to explore public discourse dynamics, identify causes and implications, and formulate recommendations grounded in Islamic economic principles. A netnographic method was employed, analyzing 13 YouTube videos and 21,470 public comments from November to December 2025 using NVivo for thematic, sentiment, narrative, and discourse analysis. Findings reveal sharp polarization, with negative sentiment (96 references) dominating positive sentiment (43 references). Based on discourse analysis of these digital sources, the policy appears to generate more mafsadat than maslahah, as reflected in public discussions highlighting internal organizational tensions, dual leadership conflicts within PBNU, concerns over the moral credibility of religious leaders, threats of irreversible environmental damage in conservation areas, and issues of accountability in policy implementation. Evaluation through maqashid sharia indicates the policy contradicts hifzh ad-din, 'adl, amanah, shaffafiyyah, and hifzh al-bi'ah. The study recommends that NU reaffirm its socio-religious mission and develop an alternative economic model based on productive waqf and sharia cooperatives.